2015
DOI: 10.1111/jan.12743
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the non‐technical skills performance of scrub nurses: a prospective study

Abstract: A dedicated surgical team and patient acuity potentially influence the performance of scrub nurses' non-technical skills. Familiarity with team members foster advanced planning, thus minimizing distractions and interruptions that impact on scrub nurses' performance. Development of interventions aimed at improving non-technical skills has the potential to make a substantial difference and enhance patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 42 publications
0
55
0
1
Order By: Relevance
“…Team members may prioritize required surgical activities based on their experience, and the high surgical volume of the ophthalmology service with its rapid between‐case turnaround can inhibit communication . Work and team familiarity are crucial elements that are needed to enhance team performance and a shared mental model, and this may be lacking when there is inadequate staffing. Our research team coded the absence of the information‐exchange element when we observed silence and nonverbal communication during surgical procedures, failure to clarify requests, lack of clear verbal responses, or speaking quietly, which could be interpreted by other surgical team members as incompetence and lack of confidence that the participants would be supported by the rest of the team …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Team members may prioritize required surgical activities based on their experience, and the high surgical volume of the ophthalmology service with its rapid between‐case turnaround can inhibit communication . Work and team familiarity are crucial elements that are needed to enhance team performance and a shared mental model, and this may be lacking when there is inadequate staffing. Our research team coded the absence of the information‐exchange element when we observed silence and nonverbal communication during surgical procedures, failure to clarify requests, lack of clear verbal responses, or speaking quietly, which could be interpreted by other surgical team members as incompetence and lack of confidence that the participants would be supported by the rest of the team …”
Section: Discussionmentioning
confidence: 99%
“…The three elements that fell below the acceptable value for r wg were providing and maintaining standards ( r wg = 0.66), coping with pressure ( r wg = 0.66), and gathering information ( r wg = 0.69) . The researchers calculated the internal consistency between element ratings and category ratings and reported a mean absolute difference of M < 0.2 between all three categories, which indicated “there was good internal consistency.” 3(p206) Although the SPLINTS tool showed adequate psychometric properties in western practices, evaluation across other settings and cultures could provide additional evidence of its applicability …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Observers and training. Across the 23 studies, the most used two observers (n ¼ 11) 17,64,86,90,91,94,95,[97][98][99]101 ; nine studies had observers with a clinical background 8,9,50,64,68,86,90,93,98 ; and eight studies had observers with a nonclinical background. 50 Non-technical skills * NOTECHS 2 24,25 Oxford non-technical skills Oxford NOTECHS 6 [11][12][13]16,26,27 Revised non-technical skills Revised NOTECHS 6 [28][29][30][31][32][33] Non-technical skills (modified) NOTECHS (modified) 1 34 Oxford Non-technical skills II Oxford NOTECHS II 6 4,[35][36][37][38][39] Non-technical skills for surgeons y NOTSS 19 9,[40][41][42][43]…”
Section: Observational Teamwork Assessment For Surgerymentioning
confidence: 99%
“…The non-technical skills, as described in other studies [30] [31] [39], can be seen as the ability to think ahead, trying to imagine everything that can go wrong, and utilizing an understanding the team to primitively address these concerns. The balance between needs related to safety and patients, as explained in this study, are similar to concepts suggested by Buber [40].…”
Section: K Brodin Et Al Open Journal Of Nursingmentioning
confidence: 99%